ELECTRONIC MODULE CONTEXTUAL LEARNING IN MATHEMATICS: ANALIZING ITS IMPACT ON STUDENT SELF-EFFICACY AND PROBLEM SOLVING ABILITIES - Firmansyah, Firmansyah; Mujib, Abdul; Siregar, Rama Nida; Mathelinea, Devi (LPPM Universitas Jambi, 2025)
This study examines the impact of contextual approach-based mathematics electronic modules on students' self-efficacy and problem-solving skills. Using the Research and Development (R&D) method with a quantitative approach, the study involved 142 junior high school students. The electronic module was developed using Kvisoft Flipbook Maker with modified Dick, Carey, and Carey development models. The research instruments included a test of problem-solving ability, a self-efficacy scale, and a student response questionnaire. The validation results show that the quality of the electronic module is very good with an average score above 4.2 out of 5. Statistical analysis revealed a significant increase in students' self-efficacy (p=0.001) with an average score of 82.4 in the experimental group compared to 72.8 in the control group. Mathematical problem-solving ability also experienced a very significant increase (p=0.000) with an average score of 82.7 compared to 74.2 in the control group. The research proves the effectiveness of contextual-based electronic modules in improving students' self-efficacy and mathematical problem-solving abilities through interactive design, contextual approaches, and cognitive scaffolding.